Expression and mutagenesis studies in the Medicago truncatula iron transporter MtVTL8 confirm its role in symbiotic nitrogen fixation and reveal amino acids essential for transport - Cai, Jingya; Longo, Antonella; Dickstein, Rebecca (Frontiers in Plant Science, 2024)
The model legume Medicago truncatula establishes a symbiosis with soil bacteria (rhizobia) that carry out symbiotic nitrogen fixation (SNF) in plant root nodules. SNF requires the exchange of nutrients between the plant and rhizobia in the nodule that occurs across a plant-derived symbiosome membrane. One iron transporter, belonging to the Vacuolar iron Transporter-Like (VTL) family, MtVTL8, has been identified as essential for bacteria survival and therefore SNF. In this work we investigated the spatial expression of MtVTL8 in nodules and addressed whether it could be functionally interchangeable with a similar nodule-expressed iron transporter, MtVTL4. Using a structural model for MtVTL8 and the previously hypothesized mechanism for iron transport in a phylogenetically-related Vacuolar Iron Transporter (VIT), EgVIT1 with known crystal structure, we identified critical amino acids and obtained their mutants. Mutants were tested in planta for complementation of an SNF defective line and in an iron sensitive mutant yeast strain. An extended phylogenetic assessment of VTLs and VITs showed that amino acids critical for function are conserved differently in VTLs vs. VITs. Our studies showed that some amino acids are essential for iron transport leading us to suggest a model for MtVTL8 function, one that is different for other iron transporters (VITs) studied so far. This study extends the understanding of iron transport mechanisms in VTLs as well as those used in SNF.